2014
DOI: 10.31887/dcns.2014.16.1/dmartins
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics, metabolomics, and protein interactomics in the characterization of the molecular features of major depressive disorder

Abstract: Omics technologies emerged as complementary strategies to genomics in the attempt to understand human illnesses. In general, proteomics technologies emerged earlier than those of metabolomics for major depressive disorder (MDD) research, but both are driven by the identification of proteins and/or metabolites that can delineate a comprehensive characterization of MDD's molecular mechanisms, as well as lead to the identification of biomarker candidates of all types-prognosis, diagnosis, treatment, and patient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(24 citation statements)
references
References 96 publications
0
23
0
1
Order By: Relevance
“…Like RDoC, most part of studies with plural molecular biomarkers panels for MDD are grounded on genetic [ 31 , 32 ] or metabolomics approaches [ 33 , 34 ]. There are few studies analyzing neuroendocrine-immune targets as part of a plural biomarker panel [ 35 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like RDoC, most part of studies with plural molecular biomarkers panels for MDD are grounded on genetic [ 31 , 32 ] or metabolomics approaches [ 33 , 34 ]. There are few studies analyzing neuroendocrine-immune targets as part of a plural biomarker panel [ 35 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major depressive disorder (MDD) is a serious debilitating mental disease and leads to a high rate of suicide and economic burden. It has greatly affected the quality of life of 350 million diagnosed patients worldwide . Biological research findings have demonstrated that MDD is closely linked to the hyperactivity of the hypothalamic–pituitary–adrenal axis, hippocampal atrophy, , and glial reduction in the subgenual prefrontal cortex; however, the diagnosis of MDD is still difficult due to the high error rate .…”
Section: Introductionmentioning
confidence: 99%
“…It has greatly affected the quality of life of 350 million diagnosed patients worldwide. 1 Biological research findings have demonstrated that MDD is closely linked to the hyperactivity of the hypothalamic−pituitary−adrenal axis, 2 hippocampal atrophy, 3,4 and glial reduction in the subgenual prefrontal cortex; 5 however, the diagnosis of MDD is still difficult due to the high error rate. 6 Several methods have been used in clinical diagnosis for depression, such as a structured or semistructured interview (SDI) and the dexamethasone suppression test (DST).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, gut microorganisms are key mediators of glutamate and GABA production, with important neurotransmitter activity in the brain. Similarly, phenylalanine, another product also synthesized by some microorganisms, is the precursor of the catecholamines epinephrine, norepinephrine, and dopamine, which are involved in the pathogenesis of MDD and therapy resistance [142].…”
Section: Microbial Influence In Other Amino Acidsmentioning
confidence: 99%